2004
DOI: 10.1158/1078-0432.ccr-1083-3
|View full text |Cite
|
Sign up to set email alerts
|

Infection with Oncolytic Herpes Simplex Virus-1 Induces Apoptosis in Neighboring Human Cancer Cells

Abstract: Purpose:The antitumor efficacy of a herpes simplex virus (HSV)-1 oncolytic virus depends on the cytotoxic effect of the virus, but also on viral replication and spread within the tumor. Apoptosis is considered a defense mechanism of infected cells that minimizes the spread of viral progeny by limiting cellular production of virus. We sought to determine whether oncolytic HSV-1 infection induces apoptosis in neighboring, uninfected cells and whether manipulation of apoptosis can increase viral replication and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
45
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 62 publications
1
45
0
Order By: Relevance
“…Based on data in cell culture, it has been proposed that apoptosis of adjacent, uninfected cells might limit virus spread within a tumor. 26 While we found nuclear changes consistent with apoptosis in early infected cells on tumor sections, cells surrounding infected cells or the debris of infected cells (identified by eGFP expression) appeared healthy. It stands to reason that to improve the antitumor effects of oncolytic viruses efforts should be focused not only on being able to inject higher virus doses but also on achieving better initial virus distribution.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Based on data in cell culture, it has been proposed that apoptosis of adjacent, uninfected cells might limit virus spread within a tumor. 26 While we found nuclear changes consistent with apoptosis in early infected cells on tumor sections, cells surrounding infected cells or the debris of infected cells (identified by eGFP expression) appeared healthy. It stands to reason that to improve the antitumor effects of oncolytic viruses efforts should be focused not only on being able to inject higher virus doses but also on achieving better initial virus distribution.…”
Section: Discussionmentioning
confidence: 49%
“…Infection with replication-defective HSV recombinants that do not express early proteins causes high levels of cellular apoptosis in a cell-type-specific manner. 25 Uninfected neighboring cells may also undergo apoptosis following injection of some cell lines with NV1066, 26 and it has been proposed that such apoptosis might limit virus spread. Tumors injected with oncolytic HSV mutants often have regions of necrosis associated with HSV-infected cells, [27][28][29][30][31] and in some cases there is a concomitant increase in apoptotic cells.…”
mentioning
confidence: 99%
“…The antitumor effect of rHSV is reported to be much greater than its evident distribution throughout tumors (20)(21)(22)(23)(24)(25). HSV infection induces apoptosis in adjacent, uninfected cells in vitro and in vivo (26). The route of administration will be a critical determining factor in the efficacy of viral therapy.…”
Section: Discussionmentioning
confidence: 99%
“…21,22,24,25 Others have therefore proposed that anti-apoptosis drugs might allow infected tumor cells to resist apoptosis, at least temporarily, thus allowing greater replication of the virus and a stronger anti-tumor effect in the long term. 26 Apoptosis is a complex process, offering many target sites at which it could be inhibited. These include the various caspases, and it has previously been demonstrated that the pan-caspase inhibitor N-benzyloxycarbonylVal-Ala-Asp-fluoromethylketone (zVADfmk) can prevent HSV-1-induced apoptosis.…”
Section: Introductionmentioning
confidence: 99%